2015
DOI: 10.1037/a0037810
|View full text |Cite
|
Sign up to set email alerts
|

Acquaintance ratings of the Big Five personality traits: Incremental validity beyond and interactive effects with self-reports in the prediction of workplace deviance.

Abstract: It is widely established that the Big Five personality traits of conscientiousness, agreeableness, and emotional stability are antecedents to workplace deviance (Berry, Ones, & Sackett, 2007). However, these meta-analytic findings are based on self-reported personality traits. A recent meta-analysis by Oh, Wang, and Mount (2011) identified the value of acquaintance-reported personality in the prediction of job performance. The current investigation extends prior work by comparing the validities of self- and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 38 publications
(66 reference statements)
2
53
0
Order By: Relevance
“…In accordance with the conservation of resources theory, emotional stability is a resource which can be utilized to reduce behavioral strain. The results support earlier studies which revealed that the lack of emotional stability leads to engagement in WDB (Gonzalez-Mulé et al, 2013;Hudson et al, 2012;Kluemper et al, 2015). Less emotionally stable individuals are more likely to encounter negative emotional states, such as anxiety, depression and anger that could trigger them to behave deviantly under stress and the behaviors displayed include behaviors such as tardiness, absenteeism and withholding effort.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with the conservation of resources theory, emotional stability is a resource which can be utilized to reduce behavioral strain. The results support earlier studies which revealed that the lack of emotional stability leads to engagement in WDB (Gonzalez-Mulé et al, 2013;Hudson et al, 2012;Kluemper et al, 2015). Less emotionally stable individuals are more likely to encounter negative emotional states, such as anxiety, depression and anger that could trigger them to behave deviantly under stress and the behaviors displayed include behaviors such as tardiness, absenteeism and withholding effort.…”
Section: Discussionsupporting
confidence: 89%
“…Further, discriminant validity was also proved by comparing the model fitness of the six-factor model with the one-factor model. The goodness of model fit of the six-factor model (RMR = .053, GFI = .844, AGFI = .813, CFI = .909, RMSEA = .053) is better than the one-factor model's (RMR = .062, GFI = .834, AGFI = .805, CFI = .899, RMSEA = .61), thereby proving discriminant validity (Kluemper, McLarty, & Bing, 2015). Additionally, discriminant validity also got established by comparing the variance extracted with squared correlations amongst different constructs (Fornell & Larcker, 1981).…”
Section: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 92%
“…Most of these studies took mainly into account the traits within the Big Five. It was found that CWB is related to high neuroticism, low agreeableness and low conscientiousness [2,3]. In recent years, the interests of researchers have turned toward the 'dark traits' of personality, treated as complementary to the traits belonging to the Big Five [4].…”
Section: Introductionmentioning
confidence: 99%